Chess Not Checkers: Complexities Within the Myeloid Response to the Acute Kidney Injury Syndrome - Nash, William T.; Okusa, Mark D. (Frontiers in Medicine, 2021)
Immune dysregulation in acute kidney injury (AKI) is an area of intense interest which promises to enhance our understanding of the disease and how to manage it. Macrophages are a heterogeneous and dynamic population of immune cells that carry out multiple functions in tissue, ranging from maintenance to inflammation. As key sentinels of their environment and the major immune population in the uninjured kidney, macrophages are poised to play an important role in the establishment and pathogenesis of AKI. These cells have a profound capacity to orchestrate downstream immune responses and likely participate in skewing the kidney environment toward either pathogenic inflammation or injury resolution. A clear understanding of macrophage and myeloid cell dynamics in the development of AKI will provide valuable insight into disease pathogenesis and options for intervention. This review considers evidence in the literature that speaks to the role and regulation of macrophages and myeloid cells in AKI. We also highlight barriers or knowledge gaps that need to be addressed as the field advances.